2018
DOI: 10.1016/j.yebeh.2018.05.032
|View full text |Cite
|
Sign up to set email alerts
|

Cognition, mood and quality-of-life outcomes among low literacy adults living with epilepsy in rural Kenya: A preliminary study

Abstract: Epilepsy is frequently associated with neurocognitive impairments, mental health, and psychosocial problems but these are rarely documented in low- and middle-income countries. The aim of this study was to examine the neurocognitive outcomes, depressive symptoms, and psychosocial adjustments of people with epilepsy (PWE) in Kilifi, Kenya. We evaluated the impact of these outcomes on health-related quality of life. Self-report, interviewer-administered measures of depression (Major Depression Inventory) and qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 43 publications
3
12
0
Order By: Relevance
“…Having moderate to severe anxiety and depression, and other co-morbidities resulted in decreased quality of life in epileptic patients. This finding is supported by studies conducted in China [ 52 ], Ethiopia [ 31 , 49 ], and Kenya [ 53 ]. This could be due to the effect of these problems on quality of life, particularly, in the domains of lethargy/fatigue, and emotional well-being [ 53 ].…”
Section: Discussionsupporting
confidence: 71%
“…Having moderate to severe anxiety and depression, and other co-morbidities resulted in decreased quality of life in epileptic patients. This finding is supported by studies conducted in China [ 52 ], Ethiopia [ 31 , 49 ], and Kenya [ 53 ]. This could be due to the effect of these problems on quality of life, particularly, in the domains of lethargy/fatigue, and emotional well-being [ 53 ].…”
Section: Discussionsupporting
confidence: 71%
“…The association between comorbid mental disorders and poor quality of life is consistent with the findings of previous studies carried out in both high-income and LMICs [ 7 , 12 , 13 , 17 ]. Higher seizure frequency has also been shown to be associated with poor quality of life [ 12 ], although some studies found that comorbid mental disorders existed despite good control of seizures [ 12 ].…”
Section: Discussionsupporting
confidence: 91%
“…Working memory impairment is well-documented in both children ( Hernandez et al, 2002 ; Myatchin and Lagae, 2011 ; Sherman et al, 2012 ; Braakman et al, 2013 ; Longo et al, 2013 ) and adults ( Hermann and Seidenberg, 1995 ; Black et al, 2010 ; Mwangala et al, 2018 ) with epilepsy. WM impairment is common across epilepsy types, manifesting in primary generalized epilepsies ( Swartz et al, 1994 ), temporal lobe epilepsy (TLE) ( Stretton and Thompson, 2012 ), and frontal lobe epilepsy (FLE) ( Swartz et al, 1994 ).…”
Section: Wm In Epilepsymentioning
confidence: 99%